Urticaria after intracervical dinoprostone gel: challenges of allergy testing in pregnancy - Pandey, Niharika; Choudhury, Satish; Gedam, Prachi; Mangani, Deepika; Gupta, Avantika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Hypersensitivity reactions to prostaglandins are rare but can pose significant risks during pregnancy. True type 1 hypersensitivity reactions are IgE-mediated, while pseudo-allergic reactions mimic these responses without involving immune pathways, making clinical differentiation challenging. Dinoprostone is commonly used for cervical ripening, with well-documented side effects; however, severe allergic reactions remain rare. We report a case of a 25-year-old primigravida induced at 39 weeks of gestation with 0.5 mg intracervical dinoprostone gel for oligohydramnios. Three hours post-administration, she developed widespread maculopapular rashes over her arms, legs, and abdomen, accompanied by itching. There were no signs of facial swelling, respiratory distress, or gastrointestinal symptoms, though mild hypotension and tachycardia were noted. The reaction was managed with intravenous chlorpheniramine, leading to partial resolution. An emergency caesarean section was later performed due to non-reassuring fetal heart rate and thick meconium. Urticaria completely resolved within 3 days with oral levocetirizine. This presentation suggested a possible pseudo-allergic reaction to dinoprostone, as patient lacked systemic features typical of IgE-mediated anaphylaxis. Although skin testing could confirm hypersensitivity, it carries considerable risk in pregnancy, including potential anaphylaxis, infection, and diagnostic uncertainties due to altered immune responses and test variability. This case highlights the importance of clinical vigilance in diagnosing and managing hypersensitivity reactions in pregnancy, where confirmatory testing may not be feasible. Close monitoring after dinoprostone administration is essential to ensure prompt identification and management of adverse reactions for maternal and fetal safety.